Characterization of the problem of solid waste management at National University of San Marcos - Pacheco Abad, Renán (2011)
On the university campus of the National University of San Marcos-UNMSM, there is a serious problem of accumulation of solid waste without separating, explained for various reasons: the lack of infrastructure for minimum separation, regulations to monitor compliance, concrete actions to give them utility, and an adequate solid waste management program. The objective of this work is to carry out a preliminary diagnosis that allows knowing the characteristics of the problem, a diagnosis of the knowledge and attitude of the university community, in order to obtain the necessary information for the definition and approach of the methodology to be followed for the formulation of the Comprehensive Plan of Environmental Management of Solid Waste-PIGARS that corresponds to the level and prestige of the UNMSM. Solid waste management involves planned work, so it is urgent to implement a comprehensive solid waste management program (PIGARS), supported by an infrastructure that minimizes its negative impact, such as a single collection center, separation at source, collection selective, door to door, acquisition of weed shredder machine.